Workplace Bullying as a Predictor of Disability Retirement: A Prospective Registry Study of Norwegian Employees. Issue 7 (July 2017) - Nielsen, Morten Birkeland; Emberland, Jan Shahid; Knardahl, Stein
Abstract : Objective: The aim of this study was to determine 1) whether bullying is related to all-cause disability retirement, 2) whether bullying contributes to the variance in disability retirement above high job demands and lack of job control, and 3) to establish gender differences in the relationship. Methods: Survey data from 14, 501 Norwegian employees on exposure factors linked to registry data on all-cause disability retirement. Results: Bullying significantly predicted risk of disability retirement (hazard ratio = 1.55; 95% confidence interval = 1.13 to 2.12). This relationship remained statistically significant after adjusting for job demands and lack of job control. Women had the highest risk of disability, but both bullied men and women had a higher risk of disability than nonbullied employees of the same gender. Conclusion: Bullying is a risk factor for disability retirement. Measures taken to prevent bullying may be beneficial for reducing both health problems and disability retirement.